GAMBARAN SARANA PRASARANA PENDUKUNG PERILAKU HIDUP BERSIH DAN SEHAT PADA SEKOLAH DASAR - Edison, Edison; Resta, Harinal Afri; Angelia, Inge (Ensiklopedia of Journal, 2023)
This research aims to provide a comprehensive overview of the facilities and infrastructure that support clean and healthy living behaviors in the environment of Primary Schools in the city of Padang. Clean and healthy living behaviors play a crucial role in ensuring the health and well-being of students in schools. In this context, this study involves observations, interviews, and document analysis to identify the types of facilities and infrastructure present in Primary Schools in Padang, with a sample size of 11 schools, focusing on 8 indicators of Healthy and Clean Living Behaviors (PHBS) in accordance with the Minister of Health Regulation No. 2269/Menkes/PER/XI/2011 on PHBS Development Guidelines.The research findings indicate that several factors influence the formation of clean and healthy living behaviors in primary schools. Sanitation facilities, such as toilets and handwashing stations, play a primary role in shaping cleanliness habits. Additionally, the availability of spaces for physical activities and sports, as well as a clean environment, also encourage students to adopt a healthy lifestyle. However, challenges related to supporting facilities and infrastructure were also identified. Limited access to adequate sanitation facilities and the lack of facility maintenance pose obstacles to developing clean and healthy living behaviors among students.Therefore, efforts are needed to improve and maintain the facilities and infrastructure that support clean and healthy living behaviors in primary schools. In order to enhance the quality of health education in primary schools, this research contributes valuable information regarding the description of facilities and infrastructure that support clean and healthy living behaviors. It is hoped that the results of this study can serve as a guide for policy development and strategies to create a healthier school environment and support the holistic development of students in the city of Padang.